Implementation of the problem-based learning model to improve students' mathematical problem-solving skills - Kholisah, Saniah Afiqoh; Anggraini, Rini Dian; Kartini (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2024)
This study aims to improve the learning process and students' mathematical problem-solving skills through the implementation of the Problem-Based Learning (PBL) model. The research employed a classroom action research design, conducted over two cycles in collaboration with a mathematics teacher. The subjects were students of class IX B at UPT SMP Negeri 2 Bangkinang Kota during the first semester of the 2023/2024 academic year. Research instruments included mathematical learning tools (syllabus, lesson plans, and student worksheets) and data collection tools (observation sheets and mathematical problem-solving tests). Data analysis combined qualitative descriptive analysis and quantitative descriptive statistical analysis. The results indicate that the implementation of PBL improved both the learning process and students' mathematical problem-solving skills. The average N-gain score increased from 0.42 (medium classification) in cycle I to 0.72 (high classification) in cycle II. Furthermore, the students' average score improved from 63.44 in cycle I to 84.56 in cycle II. These findings conclude that the Problem-Based Learning model effectively enhances the learning process and mathematical problem-solving skills of class IX B students at UPT SMP Negeri 2 Bangkinang Kota.